Model Pengembangan Wisata Pantai Maribaya, Tegal, Jawa Tengah - Rahmat Firdaus Bouty (Universitas Muslim Indonesia, 2022)
Based on data from information from the Ministry of Home Affairs 2018, Indonesia had 16,056 islands in 2017. On Java itself, there are several beaches managed by local and private governments. In West Java Province precisely in Tegal Regency, Kramat District, Maribaya Village has a potential one named Maribaya Beach. This beach has uniqueness because it is opposite the ship's workshop so it can be a tourist attraction. The coastal community is struggling to be able to realize new ideas so that it is carried out according to the character and value of Maribaya Beach such as the wreck of the ship and a large pine tree. The community in question is coastal observers and local village governments who play a role in advancing Maribaya Beach. The main objective of this research is to compile a model of development or master plan and recreation of Maribaya Beach, Kramat District, Tegal Regency, Central Java Province as an effort to increase the competitiveness of innovation and science. The results of this study include design strategies developed through an understanding of several case studies, field conditions, and community specifics around Maribaya Beach. The value of this study comes from its potential from the community for the benefit of designing and developing strategies, plans, agendas, and alternatives that are more effective to improve the quality of the coastal community of Maribaya coastal coast.